Angels & Demons A Breathless Real Time Adventure - Brown, Dan; Dan Brown (London, United Kingdom Corgi Books, 2000)
In Angels & Demons, Harvard symbologist Robert Langdon is summoned to a Swiss research facility to analyze a mysterious symbol seared into the chest of a murdered physicist. He discovers evidence of the resurgence of the Illuminati, a secret brotherhood thought extinct. The Illuminati has surfaced to carry out a vendetta against the Catholic Church, threatening to destroy Vatican City with a time bomb of antimatter. Langdon teams up with scientist Vittoria Vetra to follow a trail of ancient symbols across Rome, racing against time to prevent a catastrophe.
Angels & Demons introduces the character of Robert Langdon, a Harvard symbologist. The novel delves into themes of science versus religion, secret societies, and historical conspiracies. It is notable for its use of ambigrams and references to real-world locations and organizations, such as CERN and the Vatican. The book was adapted into a feature film released in 2009
Keywords: ANGELS & DEMONS - Dan Brown